Kolaborasi Pengembangan Pariwisata Pacu Jalur Berbasis Masyarakat di Kabupaten Kuantan Singingi - Ego Pernanda Saputra; Adianto Adianto (Pusat Riset dan Inovasi Nasional, 2024)
Currently tourism in Indonesia is growing very rapidly. The role of stakeholders is very necessary in planning a tourist destination because it can help to develop tourism potential in a village. This research focuses on discussing community based tourism development collaboration at Pacu jalur events in Kuantan Singingi Regency and what factors inhibit collaboration in community-based tourism development at Pacu jalur events in Kuantan Singingi Regency. The aim of this research is to find out how collaborative community based tourism development is at the pacu jalur event in Kuantan Singingi Regency and what are the inhibiting factors for collaboration in community based tourism development at the pacu Jalur event in Kuantan Singingi Regency using the pentahelix model of 5 stakeholders. This study used qualitative research is descriptive methods. This research found that the roles of each stakeholder are: academics focus on tourism planning based on existing theories, the government focuses on policy makers in developing tourism potential, business actors as nails in creating added value and maintaining economic growth in the surrounding area, and the role of the role of the community is to help manage tourism potential and the role of the media is to promote and help inform the wider community about the spur route. The research results found that collaborative governance has run quite optimally. The inhibiting factors in community-based tourism development collaboration were also revealed, namely, a) Lack of pentahelix coordinators in the development of Pacu jalur tourism, b) Lack of support for road infrastructure access in the development of Pacu jalur tourism, c) Low creativity and innovation at Pacu jalur tourism locations. Through this research, it can be used as an evaluation so that it can increase the efforts of the Department of Tourism and Culture in developing tourist attractions leading to national events.